Establishing a co-production framework between researchers and the autistic community: embracing the neurodiversity paradigm - PI Lei, QING Shan (Xin yixue)
Autism research is evolving from a medical paradigm， which emphasizes deficits and interventions， to a neurodiversity paradigm that values autism as an integral part of human diversity. Historically， the medical paradigm’s focus on “rescue” efforts has distanced researchers from the autistic community， often failing to address the community’s real needs. In contrast， the neurodiversity paradigm advocates a comprehensive understanding of autism and the adoption of participatory research practices. This shift encourages active collaboration between researchers and autistic individuals， fostering inclusive knowledge production that is both meaningful and impactful for the autistic community. However， achieving this collaborative approach requires dismantling social barriers， such as power imbalances， that hinders effective partnership. This article explores the principles and practice of a neurodiversity-aligned participatory research approach and proposes a co-production framework designed to support researchers and the autistic community in advancing autism research that is relevant， respectful， and responsive.